Effects of Bithiophene Imide Fusion on the Device Performance of Organic Thin‐Film Transistors and All‐Polymer Solar Cells. (3rd November 2017) - Wang, Yingfeng; Yan, Zhenglong; Guo, Han; Uddin, Mohammad Afsar; Ling, Shaohua; Zhou, Xin; Su, Huimin; Dai, Junfeng; Woo, Han Young; Guo, Xugang
Abstract: Two new bithiophene imide (BTI)‐based n‐type polymers were synthesized. f‐BTI2‐FT based on a fused BTI dimer showed a smaller band gap, a lower LUMO, and higher crystallinity than s‐BTI2‐FT containing a BTI dimer connected through a single bond. s‐BTI2‐FT exhibited a remarkable electron mobility of 0.82 cm 2 V −1 s −1, and f‐BTI2‐FT showed a further improved mobility of 1.13 cm 2 V −1 s −1 in transistors. When blended with the polymer donor PTB7‐Th, f‐BTI2‐FT‐based all‐polymer solar cells (all‐PSCs) attained a PCE of 6.85 %, the highest value for an all‐PSC not based on naphthalene (or perylene) diimide polymer acceptors. However, s‐BTI2‐FT all‐PSCs showed nearly no photovoltaic effect. The results demonstrate that f‐BTI2‐FT is one of most promising n‐type polymers and that ring fusion offers an effective approach for designing polymers with improved electrical properties.